2017
DOI: 10.1097/md.0000000000006884
|View full text |Cite
|
Sign up to set email alerts
|

Third-line chemotherapy in advanced gastric cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…To our knowledge, JAVELIN Gastric 300 and KEYNOTE-061 are the only randomised trials comparing anti-PD-1/PD-L1 antibodies with chemotherapy in patients with previously treated GC/GEJC. Although not approved for use in the third-line setting, chemotherapy is frequently used on the basis of several studies that have suggested improved patient outcomes relative to BSC or placebo [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, JAVELIN Gastric 300 and KEYNOTE-061 are the only randomised trials comparing anti-PD-1/PD-L1 antibodies with chemotherapy in patients with previously treated GC/GEJC. Although not approved for use in the third-line setting, chemotherapy is frequently used on the basis of several studies that have suggested improved patient outcomes relative to BSC or placebo [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Chemotherapy is one of the main additional methods in treatment, but the rise of drug resistance restricts its effect and might lead to treatment failure. [6][7][8] In order to solve this problem, we need to study the mechanisms of the chemotherapy resistance and find solutions.…”
Section: Introductionmentioning
confidence: 99%
“…advanced gastric cancer who underwent third line chemotherapy had superior results to those who received optimal supportive care (10), but there is no comparison among different third line treatment, such as apatinib, nivolumab, and trifluridine/tipiacil. Based on the present analysis, nivolumab appeared to be the best option for OS.…”
Section: Discussionmentioning
confidence: 99%
“…Both irinotecan and taxane have been accepted as second line therapy (5). Increasing evidence from phase II or III trials have proved that salvage systematic therapy, including chemotherapy, target therapy, or checkpoint inhibitor therapy can prolong survival in patients who do not succeed with second line therapy (6)(7)(8)(9)(10), when compared with a placebo. But it is hard for clinicians to determine the best therapy, because there are no head-tohead randomized clinical trials (RCTs) to evaluate the efficacy and safety among the available third line therapies.…”
Section: Introductionmentioning
confidence: 99%